2022
DOI: 10.3390/app12042089
|View full text |Cite
|
Sign up to set email alerts
|

Bruxism Influence on Volume and Interleukin-1β Concentration of Gingival Crevicular Fluid: A Preliminary Study

Abstract: Bruxism is occlusal behaviour that often leads to stomatognathic system overload. Inflammatory markers in the periodontium are detectable in the gingival crevicular fluid (GCF). GCF production fluctuates due to various factors. Our study aimed to assess the effect of tooth clenching or grinding on GCF volume and proinflammatory IL-1β concentration in GCF. This pilot study was carried out on 20 participants aged 21 to 28 with good general health (per 10 people studied and control groups). GCF volume was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…GCF is a transudate or exudate of human plasma and depends on vascular permeability, which increases with the inflammation of the periodontal tissue [ 40 , 41 ]. Secreted in site of inflammation gives the best information about the ongoing inflammatory condition [ 40 , 42 , 43 ]. In our study, the evaluation of Np concentrations and TA revealed different results.…”
Section: Discussionmentioning
confidence: 99%
“…GCF is a transudate or exudate of human plasma and depends on vascular permeability, which increases with the inflammation of the periodontal tissue [ 40 , 41 ]. Secreted in site of inflammation gives the best information about the ongoing inflammatory condition [ 40 , 42 , 43 ]. In our study, the evaluation of Np concentrations and TA revealed different results.…”
Section: Discussionmentioning
confidence: 99%
“…Bodily functions disturbed by bruxism can include, among other things, increased activity of the masticatory muscles, masticatory muscle hypertrophy (especially of the masseter), scalloped or burning tongue, linea alba on the cheeks along the bite line, tooth tissue damage (enamel cracks, abfractions, excessive tooth wear beyond what is expected with age) [9,21,22], repeated damage to prosthetic restorations, disturbances of the amount and composition of secreted saliva, an often severe manifestation of craniofacial pain, stiffness of the TMJ [23,24], gingival fluid secretion increase [25], bone exostoses, and periodontal leases (increased tooth mobility, gingival recessions) [21-23, 26, 27].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Due to the variety of symptoms and the overlaps with other conditions, a bruxism diagnosis requires careful evaluation that includes questionnaires, records of past bruxism episodes, and thorough examination. To confirm the diagnosis of bruxism, there are two different methods: a non-instrumental method based on the patient's description of symptoms, questionnaires, medical history, and clinical examinations [21,25,[42][43][44]; and an instrumental method using electromyography (EMG) and polysomnography, showing muscle activity during sleep and the lack of associated epileptic activity [1].…”
Section: Diagnosismentioning
confidence: 99%
“…The GCF volume (GCFV) is proportional to the severity of periodontal inflammation, and the release and components of GCF provide significant information about periodontal disease development (10). GCFV can also change in conditions such as smoking (11), bruxism (12), diabetes, and periodontal disease (13).…”
Section: Introductionmentioning
confidence: 99%